Photoredox catalyzed C(sp3)C(sp) coupling of dihydropyridines and alkynylbenziodoxolones. Issue 45 (7th November 2019) - Liang, Shengzong; Angnes, Ricardo A.; Potnis, Chinmay S.; Hammond, Gerald B.
Graphical abstract: A visible light mediated deformylative alkynylation of aldehydes is presented. Under photo irradiation, 1, 4-dihydropyridine (DHP), derived from an aldehyde, generated a C(sp 3 )- radical which couples with alkynylbenziodoxolone, to generate an alkyl coupling product. This strategy is mild and easy to operate, and a wide range of functional groups are tolerated. Highlights: Certain cross couplings reactions may be challenging or require chemical adjuvants. Photoredox C(sp 3 )C(sp) coupling of DHPs and alkynylbenziodoxolones is feasible. The procedure achieves formal deformylative CC bond formation. Functional group tolerance is noteworthy. Abstract: A visible light mediated deformylative alkynylation of aldehydes is presented. Under photo irradiation, 1, 4-dihydropyridine (DHP), derived from an aldehyde, generated a C(sp 3 )- radical which couples with an alkynylbenziodoxolone to generate an alkyl substituted alkyne coupling product. This strategy is mild and easy to operate, a wide range of functional groups were tolerated, and 16 examples of products with 35–86% yields were obtained.